The association of hair dye use with sociodemographic and lifestyle factors in the Dutch general population: a cross-sectional questionnaire-based study - Rosenberg, Fieke; Ofenloch, Robert; van der Most, Peter J.; Loman, Laura; Snieder, Harold; Schuttelaar, Marie L. A. (Contact dermatitis, 2026)
Background Sociodemographic and lifestyle factors may be related to the use of cosmetic procedures with potential adverse skin effects, such as hair dye use. Objectives To investigate the association of several sociodemographic and lifestyle factors with (adverse skin reactions to) hair dye use in the Dutch general population. Methods This cross-sectional study used questionnaire-derived data from the population-based Lifelines cohort regarding lifetime hair dye use and adverse skin reactions (n = 70 987). Logistic regression analyses investigated associations of sociodemographic factors (ethnicity, hair colour, marital status, educational attainment, income, neighbourhood socioeconomic status) and lifestyle factors (smoking, alcohol consumption, and body mass index [BMI]) with adverse skin reactions to hair dye use. Results Hair dye use was significantly positively associated with having dark blonde or brown hair colour, lower educational attainment, smoking, daily alcohol consumption and higher BMI. Hair dye use was significantly negatively associated with having red or auburn hair colour. Furthermore, adverse skin reactions to hair dye were significantly positively associated with higher BMI. Conclusions Our findings highlight several positive associations between sociodemographic and lifestyle factors and both hair dye use and its adverse skin reactions. Notably, elevated BMI was consistently positively associated with both hair dye use and adverse skin reactions.